Multi-sector stakeholder consensus on tackling the complex health and social needs of the growing population of people leaving prison in older age - Ye In (Jane); Stephen Hampton; Adrienne Lee Withall; Phillip Snoyman; Katrina Forsyth; Tony Butler (BMC, 2024)
Abstract Background As populations age globally, cooperation across multi-sector stakeholders is increasingly important to service older persons, particularly those with high and complex health and social needs. One such population is older people entering society after a period of incarceration in prison. The 'ageing epidemic' in prisons worldwide has caught the attention of researchers, governments and community organisations, who identify challenges in servicing this group as they re-enter the community. Challenges lie across multiple sectors, with inadequate support leading to dire consequences for public health, social welfare and recidivism. This is the first study to bring together multi-sector stakeholders from Australia to form recommendations for improving health and social outcomes for older people re-entering community after imprisonment. Results A modified nominal group technique was used to produce recommendations from N = 15 key stakeholders across prison health, corrections, research, advocacy, aged care, community services, via online workshops. The importance and priority of these recommendations was validated by a broader sample of N = 44 stakeholders, using an online survey. Thirty-six recommendations for improving outcomes for this population were strongly supported. The key issues underlying the recommendations included: improved multi-stakeholder systems and services, targeted release preparation and practices that ensure continuity of care, advocacy-focused initiatives in the community, and extended funding for effective programs. Conclusions There is consensus across stakeholders on ways forward, with intervention and policy updates required at the individual, systems and community levels. These recommendations entail two important findings about this population: (1) They are a high-needs, unique, and underserved group at risk of significant health and social inequity in the community, (2) Multi-sector stakeholder cooperation will be crucial to service this growing group.